UI/UX Redesign Using User-Centered Design (UCD) Method on Fatsecret Website - Asep Pujiyono, Putra Wira Pratama Ramadhan; Muhamad Irsan (Indonesian Journal on Computing (Indo-JC), 2024)
Weight loss websites have become a primary source of information for individuals looking to change their diet and achieve a healthy weight by offering a variety of features, content, and UI/UX redesigns to help users achieve their health goals using User-Centered Design (UCD). This study aims to find out trends and characteristics using the Fatsecret Website. FatSecret is a website that has a food calorie counter feature used to calculate the number of calories eaten each day. This research analyzes the improvement of the website's quality in terms of User Interface (UI) and User Experience (UX) by redesigning it using the UCD method. This study aims to produce analysis and design of the UI and UX on the Fatsecret Website. The method used is User-Centered Design, divided into 4 stages. The results of the UI/UX design include solutions to problems found, such as adding a workout feature, redesigning the reminder feature, and placing it outside to make it easier to see. The addition of a workout feature makes it easier for users to lose weight by exercising and managing calories simultaneously. The main colors of the Fatsecret logo, white and green, inspired the prototype's color scheme.